O paradigma jusambiental nas relações de emprego e seu impacto na reforma trabalhista brasileira - Adelson Silva dos Santos (2023)
This project aims to present the assumptions and consequences of applying the jus environmental paradigm in employment relations, as a basis for preserving the collective protection of work, promoting the health and safety of workers, in light of the reform promoted by Law No. 13,457 , of July 13, 2017, guided by liberal assumptions and private self-regulation. It is presented how the immediate protection of the work environment is more effective for the mediate protection of worker health and safety. It is therefore demonstrated that the principles of environmental law consistent with the labor field, as pillars of the jus-environmental paradigm itself, must be used by the interpreter of the norm (labor reform), due to the necessary promotion of collective labor protection. Therefore, the provisions introduced by the labor reform cannot limit state action only to the so-called protective labor right, which is individualistic in nature. Therefore, it is necessary to make compatible the implementation of decent work, with the guarantee of a healthy and safe work environment, with respect for free initiative, so that private self-regulation is permeated by the soundness of collective environmental protection of work. In other words, the compatibility of state intervention with collective private self-regulation for the protection of the work environment.